A Systematic Review of Affordance Theory in Digital Transformation Research: Evidence from 2020–2025 - Yolanda Noviasari Maramis; Sambas Ade Kesuma; Firman Syarif; Iskandar Muda (Ilmu Bersama Center, 2025)
This study presents a Systematic Literature Review (SLR) of research applying Affordance Theory in the context of digital technology from 2020 to 2025. A total of 49 peer-reviewed studies were analyzed to identify dominant constructs, mediating mechanisms, boundary conditions, and research gaps. The findings show that perceived, actualized, and technological affordances serve as core constructs explaining how digital features enable or constrain user behavior. Mediating factors such as trust, engagement, and learning orientation influence how affordances translate into digital outcomes, while contextual conditions such as organizational culture and technological complexity shape their effectiveness. Despite its growing application, the literature remains fragmented, with limited theoretical integration and methodological diversity. Future research should adopt process-oriented, longitudinal, and mixed-method approaches to enhance the explanatory power of Affordance Theory. This review contributes to a clearer theoretical understanding of how digital affordances drive behavioral and organizational transformation in the evolving digital era.